Nação, herói e paisagem: O sertanejo, de José de Alencar - Macêdo Júnior, Ulisses (2012)
This dissertation aims to make a critic appreciation of the work o sertanejo by José de Alencar, observing the process of construction of an identity and paisangens sertanejas, erected from the confluence of elements of European culture and local representations of popular stamp. From this perspective of correlation are analyzed some nuances of medieval literature, suzerainty and vassalage, as well as the influences of the environment with the advance of the cattle rising, configured in the rimance of boi, besides the ubiquitous role of Arnaldo character, this epic hero supreme sertaneja. For this purpose, is used as theoretical support, critical and historical, other works of the own José de Alencar, and o nosso cancioneiro and como e por que sou romancista, the revaluation of the concept of landscape of the humanistic geography and cultural by Paul Claval; the symbols of material imagination and dynamics of Gaston Bachelard, the concepts of the hero of Joseph Campbell, in addition to general contributions of Karin Volobuef and Valéria de Marco about the plural dimension of Romanticism; of Jerusa Pires Ferreira, Doralice Alcoforado Krab and Camara Cascudo it comes to popular culture; Jorge Araujo and Elvya Pereira in their readings of the work of José de Alencar.